Women's in Fitness Social Belonging and Physical Activity in the Context of Quality of Life - Cuprika, Aleksandra; Fernate, Andra; Cupriks, Leonids (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Forming as many interpersonal relationships as possible is one of the most important goals in peoples’ lives. Mutual physical activities create a basis for social belonging. Therefore, the goal of the study is to determine the correlation between the components of social belonging and physical activity among women in fitness. The social belonging analysis was conducted with the use of questionnaires (adopted in Latvian), and a shortened version of IPAQ to determine the levels of physical activity. The components of social belonging were defined, and several weak, but significant, correlations between these components and the level of physical activity were found. According to the data obtained in the current study we can conclude, that social belonging has positive impact on PA. Those, who more often feel the relatedness, satisfactory from interpersonal relationship and inclusion in the social groups are more physically active. In order to evaluate, how the quality of life aspect of social belonging for women in fitness correlates with physical activity, they must be taken into account.